Keepers of the House: A documentary. (21st November 2021) - Alexopoulos, Evangelia A.; Guinee, Emily P.; Stewart, Kearsley A.; Brown, Candace S.; Gold, Deborah T.; Engle, Deborah; Talenti, Francesca; Klevansky, Rhonda; Barfield, Raymond; Ross, Elizabeth; Prose, Neil S.
Abstract: Background: Our documentary, Keepers of the House, highlights ways that hospital housekeepers, typically unnoticed care team members, provide emotional support for patients and their families. This film addresses a gap in education by emphasizing the importance of valuing and reflecting on the unique lived experiences of others. Approach: We created this documentary to expose students to the experiences and perceptions of hospital housekeepers. A focus group with six hospital housekeepers informed an interview script for the film's creation. Nine additional housekeepers were then interviewed, which developed into a 15‐min documentary. Healthcare students and educators from five disciplines viewed the documentary during their institution's Medical Education Day. Evaluation: To expose students and educators to housekeepers' experiences, we designed our post‐viewing survey to address whether the housekeepers' stories impacted their understanding of the role and value of these workers. Viewers were surprised by the depth and breadth of patient–housekeeper interactions, the trauma housekeepers experienced from patient loss and the pride housekeepers take in their work. The stories that touched the viewers varied but centred on connections between housekeepers and patients. Lessons learned focused on recognizing the contributions of unseen team members. Implications: This innovative documentary amplifies the perspectives of voices rarely heard in healthcare. We aim to use this film, alongside its associated learning session, in education and grand round settings to foster discussion around empathy, valuing underrecognised team members and applying these insights in practice. This work can be disseminated to other institutions, further amplifying underrepresented narratives in healthcare.